Ensino de discriminações condicionais e avaliação de desempenhos emergentes em autistas com reduzido repertório verbal - Varella, André Augusto Borges (Universidade Federal de São Carlos, 2009)
The autism disorder is characterized by a developmental disability witch implies in severe impacts in many areas of development. One of the basic features of the autism is the impairments on language development. Considering that language is symbolic behavior and that stimulus equivalence paradigm allows a specification of symbolic behavior, the present study uses stimulus equivalence paradigm to study equivalence class formation in minimally verbal individuals with autism. In the Study 1, the generalized identity matching was investigated in five individuals with autism. The participants had the verbal and discriminative repertoires assessed by the ABLLS, PPVT-R and ABLA tests. Identity matching tasks were conducted on computer with varied sets of stimuli. Four participants (P2, P3, P4 and P5) mastered the criterion for a variety of sets and demonstrate generalized identity watching. In the Study 2, the four participants whom demonstrate generalized identity matching were taught the visualvisual arbitrary conditional relations AB and CB. All the visual stimuli were abstract forms. Two individuals (P4 and P5) did not achieve the criterion established for the AB relation, despite extensive training. P2 and P3 achieved the baseline relations and equivalence class formation was assessed, showing positive results for both participants. The results obtained show how programmed teaching promotes the acquirement of conditional discriminations and the demonstration of symbolic behavior by autistic individuals with minimal verbal repertoires.
Keywords: Educação especial; Psicologia experimental; Autismo; Discriminação condicional; Equivalência de estímulos; Comportamento verbal; Autism; Conditional discrimination; Stimulus equivalence; Verbal behavior; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL